Evaluasi Pengelolaan Keuangan Desa Berbasis Sistem Keuangan Desa (SISKEUDES) di Desa Tenggela - Nur Cahyani Dehi; Nur Hidayah Is. Onu; Khalsja Oktaviani Kadir; Sahmin Noholo (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to evaluate village financial management based on the Village Financial System (SISKEUDES) in Tenggela Village. The research employed a qualitative method with a descriptive approach to examine the implementation of village financial management covering the stages of planning, implementation, administration, reporting, and accountability. Data were collected through observation, interviews, and documentation. The findings indicate that village financial management in Tenggela Village has generally been implemented in accordance with the provisions of the Minister of Home Affairs Regulation Number 20 of 2018. The implementation of SISKEUDES has contributed to improving administrative order, facilitating transaction recording, and accelerating the preparation of village financial reports. However, several challenges remain, including limited human resource capacity, dependence on specific operators, administrative delays, and inadequate internet network quality. Furthermore, the transparency aspect requires improvement, as financial reports have not been optimally disclosed to the public through digital media. Therefore, enhancing the capacity of village officials and optimizing the use of information technology are necessary to support more transparent, accountable, and effective village financial management.